Limited Knee-Joint Range of Motion in Patients With Tophaceous Gout Improved With Medical Treatment: A 18-Months Follow Up - Lu, Chuan-Chin; Wei, James Cheng-Chung; Chang, Cheng-Ang; Chen, Chih-Ming; Tsai, Sen-Wei; Yeh, Chih-Jung (Frontiers in Medicine, 2020)
Objectives: Tophi may occur within the knee joint causing limited knee-joint range of motion (knee motion). We investigated the relationships between knee motion, total intra-articular tophi size (tIA-tophi), and total subcutaneous tophi size (tSC-tophi) and determined knee motion improvement after continual urate-lowering therapy (ULT). Methods: A total of 26 patients with tophaceous gout and limited knee motion were enrolled. Inclusion criteria were age ≤ 60 years and preserved knee joint space on a plain radiograph. tSC-tophi were measured using a Vernier caliper and tIA-tophi were measured using magnetic resonance imaging software. All patients were re-evaluated after 12 to 24 months of continual ULT. Upon initial visit, knee motion was related to tIA-tophi and tSC-tophi. Results: After an average of 18.2 months of ULT, the reduction in tSC-tophi was correlated with the reduction in tIA-tophi (P = 0.014, r = 0.395) and improvement in knee motion (P = 0.038, r = 0.408). Knee motion can be eventually improved even in cases of poor initial knee motion (P = 0.000, r = −0.911) or large initial tIA-tophi (P = 0.014, r = 0.476). Tophi can occur in any location within the knee joint. In multiple lineal regression, knee motion was predicted to improve 8.39° for every 10 centimetres of tIA-tophi reduction. Conclusions: Limited knee motion in patients with intra-articular tophi improved with medical treatment, regardless of initial severity. Furthermore, tSC-tophi can be used as an indicator of limited knee motion and their improvement as a predictor of knee motion improvement.